Exposure to emissions from municipal solid waste incinerators and miscarriages: A multisite study of the MONITER Project. (May 2015) - Candela, S.; Bonvicini, L.; Ranzi, A.; Baldacchini, F.; Broccoli, S.; Cordioli, M.; Carretta, E.; Luberto, F.; Angelini, P.; Evangelista, A.; Marzaroli, P.; Giorgi Rossi, P.; et al.
Abstract: Background: Miscarriages are an important indicator of reproductive health but only few studies have analyzed their association with exposure to emissions from municipal solid waste incinerators. This study analyzed the occurrence of miscarriages in women aged 15–49 years residing near seven incinerators of the Emilia-Romagna Region (Northern Italy) in the period 2002–2006. Methods: We considered all pregnancies occurring in women residing during the first trimester of pregnancy within a 4 km radius of each incinerator. Addresses were geocoded and exposures were characterized by a dispersion model (ADMS Urban model) producing pollution maps for incinerators based on PM10 stack measurements and for other pollution sources based on NOx ground measurements. Information on pregnancies and their outcomes was obtained from the Hospital Discharge Database. Simplified True Abortion Risks (STAR) × 100 estimated pregnancies were calculated. We ran logistic regressions adjusting for maternal characteristics, exposure to other sources of pollution, and sites, considering the whole population and stratifying by miscarriage history. Results: The study analyzed 11, 875 pregnancies with 1375 miscarriages. After adjusting for confounders, an increase of PM10 due to incinerator emissions was associated with an increased risk of miscarriage (test for trend, p = 0.042). The odds ratio for the highest quartile of exposed versus not exposed women was 1.29, 95% CI 0.97–1.72. The effect was present only for women without previous miscarriages (highest quartile of exposed versus not exposed women 1.44, 95% CI 1.06–1.96; test for trend, p = 0.009). Conclusion: Exposure to incinerator emissions is associated with an increased risk of miscarriage. This result should be interpreted with those of a previous study on reproductive health conducted in the same area that observed an association between incinerator exposure and preterm births. Highlights: A population study assessed the association of incinerator exposure with miscarriages. Exposure was estimated in the first trimester of gestation through a dispersion model. Miscarriage occurrence was measured as a proportion of all pregnancies at risk. Positive association found between exposure to incinerator and miscarriage occurrence This association was found only among women without previous miscarriages.